The substitution method works by solve one equation for some variable and then plug-in this equation into the other one.
Then in this case, we already have the first equation in the form of y=--- (solved for y). Then the next step is replace this y=2x-7 into the second equation as follows:
![\begin{gathered} 3x+4y=16 \\ 3x+4(2x-7)=16 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x315utosczoeysz99dntaxxtkzj3sdbsdm.png)
Which is the very same as the option C. Hence the answer is C) 3x+4(2x-7)=16